Implementasi Virtual Interface Menggunakan Metode EOIP Tunnel Pada Jaringan WAN PT. Indo Matra Lestari - Sidik Sidik; Ade Sudaryana; Rame Santoso (Universitas Bina Sarana Informatika, 2020)
Computer networks have become an important point in companies that have many branch offices to coordinate the transfer of data. PT Indo Matra Lestari's connection uses a VPN system using the PPTP method. Data Center is used as a VPN server, the client is the Head Office and Citereup Branch Offices. Between the Head Office and the Citereup Branch Office there is no direct connection so access to data made between the Head Office and the Citereup Branch Office is slow, because the data must pass through the Data Center before reaching its destination. Moreover, the data accessed is private to the company and only accessed on the local network. The solution used to create a direct and secure network path between the Head Office and Branch Offices is to use the EoIP Tunnel on the proxy router. Tunneling method in EoIP can make network bridging between proxy devices, EoIP Tunnel will change to Virtual Interface on the proxy router so that it is as if the proxy router is connected locally. Tunnel ID on the EoIP Tunnel functions as a tunneling path security. The application of the EoIP Tunnel makes the point to point connection point between Mikrotik devices faster in data access because the data access is directed to the destination. In order for this EoIP Tunnel connection to run optimally and well, a network management is needed in managing internet bandwidth usage